Analisis Faktor-Faktor yang Mempengaruhi Produksi Padi Petani Desa Sungai Solok Kecamatan Kuala Kampar Kabupaten Pelalawan - Hariy Laksamana; Era Kurniati (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2022)
Sungai Solok Village is one of the villages in Kuala Kampar District, with an area of 6.851 Ha which occupies the second position in producing rice in Pelalawan Regency. Has considerable potensial for increasing rice production but is still not optimal due to several factors, so it’s necessary to know how much influence it has on rice production. So it’s necessary to conduct further studies to analyze the factors that affect the level of rice production. The method used in this research is a qualitative and quantitative research method. In accordance with the problem raised, the research focus is emphasized on factor that affect production results, age, education, land area, land ownership status, and utilization of advance in communication technology. Data collection and processing techniques in this study were carried out through observation, and interviews. While the data analysis thecniques used in this research are descriptive qualitative analysis and multiple linear regression analysis. Based on this research, the factors that influence rice production in Sungai Solok Village, Kuala Kampar District, which have a significant effect are land area, while those that don’t affect are age, education, ownership status and the use of communication technology bye farmers.